A comparative analysis of the intended curriculum and its presentation in 10th grade chemistry textbooks from seven Arabic countries. Issue 2 (1st March 2017) - Khaddoor, Rouba; Al-Amoush, Siham; Eilks, Ingo
Abstract : This study investigates the nature of intended secondary chemistry curricula, as they are represented by chemistry textbooks, from seven Arabic countries: Algeria, Egypt, Jordan, Kuwait, Palestine, Saudi Arabia and Syria. The curricula are evaluated through analysis of the officially approved 10th grade chemistry textbooks used nationwide in all of these countries. The textbooks were analysed by qualitative content analysis in three cycles. The cycles focused on technical characteristics, the representation of the content, and an overall rating of the intended curriculum based on the findings from the first two rounds in connection to the ideas of the curriculum emphasis and curriculum orientation. The overall rating focuses on the orientation of the intended curricula, the emphases behind them, and indicators of any student-centred pedagogy. Our findings show that the textbooks differ widely. Some textbooks from this sample proved to be very traditional and purely organized in terms of the chemistry content with very limited connections of the content to modern aspects or applications of chemistry. The curricula in Algeria, Kuwait and Palestine were found to be of this kind. The textbooks from these countries basically operate a fundamental chemistry and structure-of-the-discipline approach. Other textbooks actually represent more modern approaches in chemistry teaching by providing a recognizable degree of contextualisation or even societal orientation. This is the case for Egypt, Syria and Saudi Arabia and, to a lesser degree, for Jordan. In the case of Palestine, the textbook focuses almost exclusively on content in technical and engineering contexts. Our analysis shows that there is no clear relationship between the intended chemistry curricula and certain characteristics in the corresponding countries, namely the regional background, the level of economic strength, and the degree of traditionalism.